Does the eHealth Literacy Scale (eHEALS) Measure What it Intends to Measure? Validation of a Dutch Version of the eHEALS in Two Adult Populations - van der Vaart, Rosalie; van Deursen, Alexander JAM; Drossaert, Constance HC; Taal, Erik; van Dijk, Jan AMG; van de Laar, Mart AFJ (JMIR Publications, 2011)
BackgroundThe Internet increases the availability of health information, which consequently expands the amount of skills that health care consumers must have to obtain and evaluate health information. Norman and Skinner in 2006 developed an 8-item self-report eHealth literacy scale to measure these skills: the eHealth Literacy Scale (eHEALS). This instrument has been available only in English and there are no data on its validity. ObjectivesThe objective of our study was to assess the internal consistency and the construct and predictive validity of a Dutch translation of the eHEALS in two populations. MethodsWe examined the translated scale in a sample of patients with rheumatic diseases (n = 189; study 1) and in a stratified sample of the Dutch population (n = 88; study 2). We determined Cronbach alpha coefficients and analyzed the principal components. Convergent validity was determined by studying correlations with age, education, and current (health-related) Internet use. Furthermore, in study 2 we assessed the predictive validity of the instrument by comparing scores on the eHEALS with an actual performance test. ResultsThe internal consistency of the scale was sufficient: alpha = .93 in study 1 and alpha = .92 in study 2. In both studies the 8 items loaded on 1 single component (respectively 67% and 63% of variance). Correlations between eHEALS and age and education were not found. Significant, though weak, correlations were found between the eHEALS and quantity of Internet use (r = .24, P = .001 and r = .24, P = .02, respectively). Contrary to expectations, correlations between the eHEALS and successfully completed tasks on a performance test were weak and nonsignificant: r = .18 (P = .09). The t tests showed no significant differences in scores on the eHEALS between participants who scored below and above median scores of the performance test. ConclusionsThe eHEALS was assessed as unidimensional in a principal component analysis and the internal consistency of the scale was high, which makes the reliability adequate. However, findings suggest that the validity of the eHEALS instrument requires further study, since the relationship with Internet use was weak and expected relationships with age, education, and actual performance were not significant. Further research to develop a self-report instrument with high correlations with people's actual eHealth literacy skills is warranted.